Digital transformation and its impact on workers' rights in Saudi Arabia: An analytical study - Yasmeen Naseer Eid Almehmadi; Amal Mohammed Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
This study examines the status of workers’ rights in the era of digital transformation in the Kingdom of Saudi Arabia. Digital transformation has shifted labor relations from traditional patterns to more modern forms, while the Saudi regulator has shown clear concern for safeguarding workers’ rights, given that workers are generally the weaker party in contractual relationships. The study addresses a central question concerning the extent to which digital transformation has affected workers’ rights in Saudi Arabia, through clarifying the concept of digital transformation and analyzing the most prominent recent developments introduced in line with the digital transformation strategy under the Saudi Labor Law.The study is divided into two sections. The first examines the concept of digital transformation, its origins, characteristics, and resulting challenges. The second discusses the contributions of digital transformation to strengthening guarantees for workers’ rights, while also highlighting the main issues related to workers’ rights in the digital environment.The study aims to define digital transformation, explain its role in regulating labor practices, and identify the most prominent digital initiatives that have contributed to strengthening workers’ rights. It also seeks to demonstrate the extent to which digital transformation is consistent with the fundamental principles of the Saudi Labor Law, and to explain the challenges created by the digital environment, particularly those related to workers’ data and privacy.The study finds that digital transformation in the labor sector has introduced new tools for protecting workers’ rights and promoting transparency, such as the Qiwa platform, the Wage Protection Program, and the requirement to authenticate employment contracts so that they may serve as enforceable instruments for claiming wages in the event of non-payment by the employer. The study concludes by recommending that the Ministry of Human Resources and Social Development organize periodic training courses for employers and workers on digital transformation, its tools, and workers’ rights.
Keywords: Digital Transformation; Saudi Labor Law; Workers’ Rights; Legal Protection; Contracts